Efficacy of Intravenous Ondansetron in Reducing Postoperative Shivering after General Anesthesia (Journal of the Bangladesh Society of Anaesthesiologists, 2019)
Background and aim of study: Postoperative shivering is one of the common problems followinggeneral anesthesia and may lead to multiple complications. The aim of this study was to observe thepreventive effect of intravenous ondansetron on postoperative shivering.Materials and methods: This randomized placebo-controlled double blind clinical trial included 80patients scheduled for elective ENT operations, randomly divided to two groups. ondansetron (4 mg)and 2ml normal saline (as placebo group) were administered immediately before the induction ofanesthesia. Anesthesia induced equivalently for all. Patients were observed incidence and severity ofshivering in postoperative period.Results: Postoperative shivering was observed in 15% of patients in ondansetron group which issignificantly lower than the saline group 50% (p